Criminal Disparity in Law Enforcement to the Performers of Judi Togel in Simalungun Court State - Mariah SM Purba; Anita Purba (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Gambling cases, especially lottery gambling, are a type of gambling that is rife in society. Courts are the last bastion for attendance seekers. Justice is not merely a place to punish but to get justice. However, the fact is that there are disparities in court decisions on the same case, namely lottery gambling at the Simalungun District Court. As for the problem is: whyCriminal disparities occur in terms of law enforcement against lottery gambling perpetrators at the Simalungun District Court and what efforts that can be made so that there is no disparity in decisions in lottery gambling cases. The research used is juridical legal research, research on laws whose position is the norm, namely the provisions of gambling crimes as regulated in the Criminal Code. Where the imposition of crimes against the same article is inconsistent, there are even disparities.